2022
DOI: 10.1098/rspb.2022.1813
|View full text |Cite
|
Sign up to set email alerts
|

High dispersal rates in hybrids drive expansion of maladaptive hybridization

Abstract: Hybridization between native and invasive species, a major cause of biodiversity loss, can spread rapidly even when hybrids have reduced fitness. This paradox suggests that hybrids have greater dispersal rates than non-hybridized individuals, yet this mechanism has not been empirically tested in animal populations. Here, we test if non-native genetic introgression increases reproductive dispersal using a human-mediated hybrid zone between native cutthroat trout ( Oncorhynchus clarkii ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…Hybridization between native and invasive species is one of the major causes of biodiversity loss (Bourret et al 2022). However, detecting hybrids was challenging when the hybrids were similar to the native species.…”
Section: Discussionmentioning
confidence: 99%
“…Hybridization between native and invasive species is one of the major causes of biodiversity loss (Bourret et al 2022). However, detecting hybrids was challenging when the hybrids were similar to the native species.…”
Section: Discussionmentioning
confidence: 99%
“…The data show the relative abundance in source populations of RBT has decreased, but recent increases have been observed in the spatial extent of hybridization (Muhlfeld et al 2017 ), indicating RBT could be coming from alternative sources. Although it is diffi cult to quantify the role that Creston National Fish Hatchery RBT have on WCT × RBT hybridization in the Flathead River, the high density of hatchery RBT in Mill Creek and the higher dispersal rates of RBT compared to WCT (Boyer et al 2008 ;Bourret et al 2022 ), suggest this facility could be a continuing source of RBT in the Flathead basin. Isolating contributions from other sources of RBT, however, is a challenging management problem.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also noted hatchery contributions in the lower portion of the drainage likely played a signifi cant role in the proliferation of RBT into the system. Hybrids of WCT × RBT have demonstrated reduced fi tness (Kovach et al 2016 ) and higher dispersal rates (Bourret et al 2022 ) compared to native WCT, likely increasing the risk of spreading maladaptive traits.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research conducted in the upper Flathead Drainage in Montana showed that Rainbow Trout hybrids have greater straying rates than Westslope Cutthroat Trout, promoting dispersal and spread (Bourret et al. 2022). One management alternative to mitigate the effects of dispersal is to intentionally isolate Westslope Cutthroat Trout populations to prevent the immigration of Rainbow Trout and hybrids.…”
Section: Introductionmentioning
confidence: 99%
“…The primary driver of the contemporary spread of admixture is the dispersal of Rainbow Trout and hybrids from established populations in historic main-stem stocking locations (Boyer et al 2008;Muhlfeld et al 2009b;Kovach et al 2015). Recent research conducted in the upper Flathead Drainage in Montana showed that Rainbow Trout hybrids have greater straying rates than Westslope Cutthroat Trout, promoting dispersal and spread (Bourret et al 2022). One management alternative to mitigate the effects of dispersal is to intentionally isolate Westslope Cutthroat Trout populations to prevent the immigration of Rainbow Trout and hybrids.…”
Section: Introductionmentioning
confidence: 99%